Benchmarking and currency risk - MASSA, Massimo (Institutional Knowledge at Singapore Management University, 2016)
We show that the currency risk embedded in the benchmarks of international mutual funds negatively affects fund performance. More specifically, a high benchmark-implied currency risk induces funds to invest in markets with less volatile currencies, leading to a higher degree of currency concentration in portfolio holdings. This currency concentration, however, departs from the optimal equity allocation strategy across countries and reduces fund performance. We document that funds resorting to high currency concentrations underperform funds with low currency concentrations by as much as 1%-2% per year.